Analysis of Civil Servant Career Development at Depok Metro Resort Police of Metro Jaya Regional Police - Minawati, Elis; Rivai, Firman Hadi; Rajab, Ridwan (Green Publisher Indonesia, 2023)
This study aims to analyze career development for civil servants and strategy based on merit system at Depok Metro Resort Police of Metro Jaya Regional Police. The research method uses qualitative research. Data collection is carried out through interview techniques and document review. The results showed that (1) the ideal merit- system-based career coaching strategy at the Depok Metro Resort Police of Metro Jaya Regional Police must include 4 important aspects in career development of civil servants using HR management theory from Sutrisno (2019) which includes aspects of planning, organizing, actuating and controlling. (2) In order to realize the civil servant career development strategy, Indonesian National Police must first compile types of structural and functional positions specifically intended for civil servants to clarify the position of career paths for civil servants in Indonesian National Police by applying 3 (three) other aspects according to Mondy's theory (2005) which includes educational qualifications, competencies and optimal performance to ensure that the management of civil servants resources in Indonesian National Police is carried out properly. In order for the Depok Metro Resort Police to implement a career development strategy, by prioritizing qualification, competence and performance for all civil servants, supported by the budget to improve the civil servants quality of Depok Metro Resort Police. With the improvement of the quality of civil servants evenly, organizational goals can be realized effectively and efficiently.